Radio diversity for reliable communication in WSNs - Kusy, B; Richter, C; Wen Hu; Afanasyev, M; Jurdak, R; Brunig, M; Abbott, D; Cong Huynh; Ostry, D (2011 10th International Conference on Information Processing in Sensor Networks, 2011)
Deployment of wireless sensors in real world environments is often a frustrating experience. The quality of radio links is highly coupled to unpredictable physical environments, leading to intermittent connectivity and frequent outages. Because link qualities are not predictable prior to deployment, current deterministic solutions to unreliable links, such as increasing network density or transmission power, do not adequately address this issue. We propose a new dual radio network architecture to improve communication reliability in wireless sensor networks. Specifically, we show that radio transceivers operating at dual widely spaced radio frequencies and through spatially separated antennas offer robust communication, high link diversity, and better interference mitigation. We show through experiments that radio diversity can significantly improve end-to-end delivery rates, network stability, and transmission costs at only a slight increase in energy cost over a single radio.